1960
DOI: 10.4141/cjss60-022
|View full text |Cite
|
Sign up to set email alerts
|

Composite Designs in Agricultural Research

Abstract: An experiment was conducted in the greenhouse using tornato plants for tesdng

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1962
1962
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…These conditions are often fulfilled satisfactorily in agronomic investigations as indicated by the fact that in six different studies conducted by the authors the fitted surfaces passed close to the treatment averages. This has also been the experience of others ( 1, 2, 9, 10,11,12,13,14).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…These conditions are often fulfilled satisfactorily in agronomic investigations as indicated by the fact that in six different studies conducted by the authors the fitted surfaces passed close to the treatment averages. This has also been the experience of others ( 1, 2, 9, 10,11,12,13,14).…”
mentioning
confidence: 59%
“…In contrast, information from ordinary factorial data estimates the interaction coefficients with greater precision than the pure quadratic coefficients. Although polynomials may be fitted to factorial data ( 14), the more convenient calculation situation produced by the "Box" designs is often very important to the agronomist who does not have ready access to computer services.…”
mentioning
confidence: 99%
“…Stated otherwise, this is a test of the planar response surface followed by a test of the improvement in fit of the equation to the data when curvature terms are introduced. Robinson and Nielsen (1960) contested this approach and suggested that all orthogonal (b1, b2, b3, b12, b13, b23) terms be tested individually. The latter approach was employed in this work because of an interest in detecting and inspecting interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Central composite design is particularly suited to experimentation with material of low variability where a sequential approach is possible. Several writers have used these designs for the study of biological problems, among which the papers of Hader et al (1957), Moore et al (1957), Miller and Ashton (1960), and Robinson and Nielsen (1960) are cited.…”
Section: Selection Of Experimental Designmentioning
confidence: 99%
“…Among the more important are plot size and experimental design (for example, a composite ora factorial design [10]). The number of factor levels used will also influence estimated process variance [2, p. 170].…”
Section: Research Costsmentioning
confidence: 99%